Potential influence of lime treated sewage sludge application on soil micro fauna and their impact on growth of Radish - Firdous, Farah; Chandel, Swati Singh; Mishra, Ekta Pathak; M. Outhman, Abubaker (International Journal of Environment, Agriculture and Biotechnology, 2024)
Lime-treated sewage sludge (LTSS) is a potential soil amendment with both benefits and drawbacks. This study aims to investigate the influence of LTSS application on soil microfauna and their subsequent impact on the growth of radish (Raphanus sativus). Soil microfauna, comprising nematodes, protozoa, and other small invertebrates, play a crucial role in nutrient cycling. LTSS application can alter soil properties like pH, nutrient availability, and organic matter content. These changes can influence the abundance and diversity of microfauna populations. LTSS can be a source of essential nutrients for radish growth, potentially leading to increased biomass and yield. Additionally, some microfauna, like certain nematodes, can promote plant growth through root-fungus interactions. High application rates of LTSS could disrupt the microfauna community, potentially reducing beneficial populations and hindering nutrient cycling. Furthermore, LTSS may contain residual heavy metals or pathogens that could negatively impact radish growth. This study hypothesizes that LTSS application will have a biphasic effect on radish growth. At moderate application rates, LTSS may enhance radish growth by stimulating beneficial microfauna populations and improving nutrient availability. However, at high application rates, negative effects on microfauna and potential heavy metal contamination might hinder radish growth.